2011
DOI: 10.1016/j.ijantimicag.2010.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in primary antimicrobial resistance of Helicobacter pylori in Finland

Abstract: The antimicrobial susceptibility of Helicobacter pylori is an important predictor of the success of eradication therapy. To evaluate recent changes in primary antimicrobial resistance of H. pylori isolated from Finnish patients, the clinical records of H. pylori-positive patients referred for endoscopy to Herttoniemi Hospital (Helsinki, Finland) during 2000-2008 were investigated retrospectively. Stored H. pylori strains from 505 patients without previous eradication therapy were tested for clarithromycin, met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…Resistance rates of metronidazole in 34 both adult and children populations were relatively high -32.8% and 25%, respectively. Metronidazole resistance remains high across Europe with no major changes in 10 years or regional distribution (4,(13)(14)(15)(16)(17)(18)(19)(20)(22)(23)(24)(25)(26)(27). It is important to point out that within our study, the tendency of increasing prevalence of clarithromycin resistance has been observed with 8.2% in adults and 17.7% in children.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Resistance rates of metronidazole in 34 both adult and children populations were relatively high -32.8% and 25%, respectively. Metronidazole resistance remains high across Europe with no major changes in 10 years or regional distribution (4,(13)(14)(15)(16)(17)(18)(19)(20)(22)(23)(24)(25)(26)(27). It is important to point out that within our study, the tendency of increasing prevalence of clarithromycin resistance has been observed with 8.2% in adults and 17.7% in children.…”
Section: Discussionsupporting
confidence: 47%
“…Resistance rates of metronidazole in both adult and children populations were relatively high – 32.8% and 25%, respectively. Metronidazole resistance remains high across Europe with no major changes in 10 years or regional distribution ().…”
Section: Discussionmentioning
confidence: 99%
“…pylori resistance to metronidazole has been associated with previous use of nitroimidazoles for gynaecological diseases, e.g. trichomoniasis and bacterial vaginosis, leading to higher resistance rates in women than in men, and use for parasitic diseases in some developing countries, leading to elevated resistance rates in inhabitants of or immigrants from these countries (McMahon et al, 2003;Koivisto et al, 2004;Mégraud, 2004aZullo et al, 2007O'Connor et al, 2010;Kostamo et al, 2011). In addition, resistance has been associated with birthplace and place of residence (Boyanova & Mitov, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is a small curved Gram-positive and microaerophilic bacterium which is fastidious to grow under ordinary growth medium [13]. Triple therapy has been recommended for the complete eradication of H. pylori [14]. Presently, the major concern around the world in medical science is that H. pylori has developed resistance against the standard antibiotics being used in the clinical practices [15].…”
Section: Introductionmentioning
confidence: 99%